Pengujian Ergonomi Berdasarkan SNI 9011:2021 dan ROSA Serta Evaluasi Lingkungan Kerja Perkantoran Berdasarkan Peraturan Menteri Kesehatan Nomor 48 Tahun 2016 di Fakultas Teknik Unsoed - Widhia Putra, Jonathan; Aulia Imran, Rani; Waluyo, Sugeng (Fakultas Teknik UMRI, 2024)
Office environments, as one of workplace, are inherently associated with potential occupational hazards that may impact the health and safety of individuals within them. According to the Ministry of Health of Indonesia Regulation No. 48 of 2016, office spaces are required to meet specific physical conditions, taking into aspects such as lighting, noise levels, air temperature, and humidity within the work environment. Various issues have been identified at the Faculty of Engineering, Universitas Jenderal Soedirman, such as malfunctioning some of air condition units, inadequate lighting, noise pollution from vehicular traffic, and complaints regarding workers' postures. Office workers are susceptible to ergonomic risks, particularly musculoskeletal disorders due to work activities (GOTRAK). This research aims to evaluate the compliance with the Ministry of Health of Indonesia Regulation No. 48 of 2016 by assessing the work environment and adhering to the standards outlined in SNI 9011:2021, which pertains to the Measurement and Evaluation of Potential Ergonomic Hazards in the Workplace. To strengthen the data and ensure the identification of potential ergonomic hazards in office settings, ergonomic assessment methods such as the Rapid Office Strain Assessment (ROSA) can be employed. The objective of this study is to measure physical environmental parameters such as lighting intensity, noise levels, and air temperature, identify GOTRAK-related complaints based on SNI 9011:2021, and provide recommendations for improvements in accordance with the Ministry of Health of Indonesia Regulation No. 48 of 2016 and SNI 9011:2021.